Self-reported prevalence of childhood allergic diseases in three cities of China: a multicenter study - Zhao Jing; Bai Juan; Shen Kunling; Xiang Li; Huang Sui; Chen Aihuan; Huang Ying; Wang Jiansheng; Ye Rongwei (BMC, 2010)
Abstract Background Several studies conducted during the 1990s indicated that childhood allergic diseases were increasing worldwide, but more recent investigations in some Western countries have suggested that the trend is stabilizing or may even be reversing. However, few data are available on the current status of allergic disease prevalence in Chinese children. The aim of the present study was to investigate the prevalence rates of asthma, allergic rhinitis, and eczema in children of three major cities of China, to determine the status of allergic diseases among Chinese children generally, and to evaluate the prevalence of allergic diseases in children of different ages. Methods We conducted a cross-sectional survey between October 2008 and May 2009 in three major cities of China (Beijing, Chongqing, and Guangzhou) to evaluate the prevalence rates of childhood allergic diseases including asthma, allergic rhinitis, and eczema, using a questionnaire of the International Study of Asthma and Allergies in Childhood (ISAAC) group. A total of 24,290 children aged 0-14 years were interviewed, using a multi-stage sampling method. To acquire data on children aged 3-14 years, we visited schools and kindergartens. To access children too young to attend school or kindergarten, we extended our survey to community health service centers. Each questionnaire was completed by a parent or guardian of a child after an informed consent form was signed. Results Of the 24,290 children in our study, 12,908 (53.14%) were males and 11,382 (46.86%) females; 10,372 (42.70%) were from Beijing, 9,846 (40.53%) from Chongqing, and 4,072 (16.77%) from Guangzhou. Our survey indicated that in Beijing, Chongqing, and Guangzhou, the prevalence rates of asthma were 3.15%, 7.45%, and 2.09%, respectively; the rates of allergic rhinitis were 14.46%, 20.42%, and 7.83%; and the rates of eczema were 20.64%, 10.02%, and 7.22%. The prevalence of allergic diseases varied with age. Asthma was relatively less common both in children aged under 2 years, and in those aged 9 years or more, in each of the three cities. The prevalence of allergic rhinitis was also lower in children younger than 2 years. The prevalence of eczema fell with age. Conclusions A marked increase in the prevalence rates of allergic diseases in China (compared with earlier data) was evident. Further studies exploring the precise causes of this increase are warranted.